Distinguishing between bacterial and aseptic meningitis in children: European comparison of two clinical decision rules. Issue 12 (26th July 2010) - Dubos, François; Korczowski, Bartosz; Aygun, Denizmen A; Martinot, Alain; Prat, Cristina; Galetto-Lacour, Annick; Casado-Flores, Juan; Taskin, Erdal; Leclerc, Francis; Rodrigo, Carlos; Gervaix, Alain; Gendrel, Dominique; et al.
Abstract : Background: Clinical decision rules (CDRs) could be helpful to safely distinguish between bacterial and aseptic meningitis (AM). Objective: To compare the performance of two of these CDRs for children: the Bacterial Meningitis Score (BMS) and the Meningitest. Design: Secondary analysis of retrospective multicentre hospital-based cohort study. Setting: Six paediatric emergency or intensive care units of tertiary care centres in five European countries. Patients: Consecutive children aged 29 days to 18 years presenting with acute meningitis and procalcitonin (PCT) measurement. Intervention: None. Main outcome measures: The sensitivity and specificity of the BMS (start antibiotics in case of seizure, positive cerebrospinal fluid (CSF) Gram staining, blood neutrophil count ≥10 ×10 9 /l, CSF protein level ≥80 mg/dl or CSF neutrophil count ≥1000 ×10 6 /l) and the Meningitest (start antibiotics in case of seizure, purpura, toxic appearance, PCT level ≥0.5 ng/ml, positive CSF Gram staining or CSF protein level ≥50 mg/dl) were compared using a McNemar test. Results: 198 patients (mean age 4.8 years) from six centres in five European countries were included; 96 had bacterial meningitis. The BMS and Meningitest both showed 100% sensitivity (95% CI 96% to 100%). The BMS had a significantly higher specificity (52%, 95% CI 42% to 62% vs 36%, 95% CI 27% to 46%; p<10 − 8). Conclusion: The Meningitest and the BMS were both 100% sensitive. This result provides level II evidence for the sensitivity of both rules, which can be used cautiously. However, use of the BMS could safely avoid significantly more unnecessary antibiotic treatments for children with AM than can the Meningitest in this population.